Repurposing agricultural support: Creating food systems incentives to address climate change - Vos, Rob; Martin, Will; Resnick, Danielle (International Food Policy Research Institute, 2022)
Agricultural support policies provide enormous transfers of resources to farmers — about US$620 billion per year worldwide in 2018–2020 — and enjoy strong political support in both developed and developing countries. Some agricultural support policies, such as input subsidies, have boosted global food production, particularly of staple crops, thereby reducing hunger and poverty. Yet, there are serious concerns about their impacts on achieving sustainable, healthy, and inclusive food systems. Redirecting, or “repurposing,” agricultural subsidies toward investments that support both increased production and greater sustainability — such as agricultural research and development (R&D) and rural infrastructure — has the potential for win-win-win gains for people, planet, and prosperity.